History of participating artistic gymnastics for women in the Summer Olympics - Sakran Hamza, Jamal; Abdel Wahed, Ali; Jabbar Ali Hussien, Ja’far; Amanah Kaittan, Mohammed (International Journal of Psychosocial Rehabilitation, 2020)
The Olympic Games is a global event that is set up after each Summer Olympics This event is in constant development, and in 1928, at the Olympic Games held in Amsterdam, women were allowed to compete on the devices designated for them and for differential competitions only Your artistic gymnastics for women differs from your artistic gymnastics for men in the number o apparatuses they have, as the men's apparatus is six and the women are four, and this sport has developed significantly over the past years It is divided now into three specializations in the Olympic program The importance of the research lies in the researcher's attempt to study the artistic aesthetics of women in a historical study in the Olympic Games and consequently to the role it played in the development of your gymnastics with the rest of your types The research aims to: 1. Learn about the history of women's participation in the ancient Olympic Games. 2: Learn about the artistic gymnastics for women. 3. Knowing the results of the women's Olympic competitions. The researcher recommends that scholars and researchers should pay more attention to conducting more studies and similar research on other sports in order to enrich national libraries with resources, as well as support researchers in order to increase research and investigation in this area and encourage the writing of historical research